Recovery trajectories following the reduction of urban nutrient inputs along the eutrophication gradient in French Mediterranean lagoons. (1st April 2019) - Derolez, Valérie; Bec, Béatrice; Munaron, Dominique; Fiandrino, Annie; Pete, Romain; Simier, Monique; Souchu, Philippe; Laugier, Thierry; Aliaume, Catherine; Malet, Nathalie
Abstract: French Mediterranean coastal lagoons have been subject to huge inputs of urban nutrients for decades leading to the eutrophication of these vulnerable ecosystems. In response to new environmental regulations, some of the lagoons have recently been the subject of large-scale management actions targeting the waste water treatment systems located on their watersheds. While the eutrophication of coastal ecosystems is well described, recovery trajectories have only recently been studied. To assess the rapidity and the extent of the effect of the remediation actions, we analysed data from a 14-year time series resulting from the monitoring of nutrients, biomass and the abundance of phytoplankton in the water column of French Mediterranean coastal lagoons covering the whole anthropogenic eutrophication gradient. Following a 50% to 80% reduction in total phosphorus (TP) and total nitrogen (TN) urban loadings from the watershed of hypertrophic and eutrophic ecosystems, the integrative parameters chlorophyll a, TN and TP, provide evidence for a rapid response (1 to 3 years) and for an almost complete recovery, suggesting no hysteresis for the eutrophic lagoon. However, our findings also show that recovery patterns depend on the eutrophication status before remediation and may include feedback responses. The different responses revealed by our results should help stakeholders prioritise remediation actions and identify appropriate restoration goals, especially in light of the targets of the Water Framework Directive (WFD). Highlights: Significant reductions in water nutrient concentrations due to decreasing urban nutrient loading. Evidence for rapid recovery (1–3 y) of hypertrophic & eutrophic lagoons found in the water column. Almost complete recovery observed for the eutrophic lagoon, highlighting no hysteresis. The recovery patterns depend on the eutrophication status before remediation. Feedback responses suggest ecosystem regimes can become unstable.